(untitled) (Research, Society and Development, 2021)
Breast cancer is the most prevalent tumor among women, and is also the leading cause of cancer death in women, reaching 2.1 million women per year worldwide. In Brazil, 66,280 new cases of breast cancer are expected to occur each year in the 2020-2022 period. The high incidence and mortality from breast cancer is related to risk factors. Thus, it is essential to know the risk factors for breast cancer through health education, whose objective is health promotion, such as the prevention of this neoplasm. Thus, this study aimed to describe an educational action aimed at preventing breast cancer in a health unit. This is a descriptive study, with a qualitative approach, of the experience report type, through the experience of nursing students during an educational action in health for a community included in a Family Health Strategy (ESF) based on the Arco de Maguerez. As a result, many women initially showed shyness and withdrawal, however, as the action took place, they were more interested and participative, giving testimonies and asking the team about the pathology. Feedback from the participation and involvement of women was massive, since they all engaged in the proposed activities. Therefore, it is observed that the participation of academics in the community is essential, dealing directly with different problems, for the development of skills and competences necessary for the profession, since this professional constantly works with health education within his assistance.